2021
DOI: 10.1002/prp2.765
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota disorder caused by diterpenoids extracted from Euphorbia pekinensis aggravates intestinal mucosal damage

Abstract: Gut microbiota disorder will lead to intestinal damage. This study evaluated the influence of total diterpenoids extracted from Euphorbia pekinensis (TDEP) on gut microbiota and intestinal mucosal barrier after long‐term administration, and the correlations between gut microbiota and intestinal mucosal barrier were analysed by Spearman correlation analysis. Mice were randomly divided to control group, TDEP groups (4, 8, 16 mg/kg), TDEP (16 mg/kg) + antibiotic group. Two weeks after intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The development of obesity is associated with a number of factors, of which the gut microbiota is one of the key factors that has received a lot of attention in recent years and is a potential target for the prevention of obesity and related metabolic diseases. And nutrients and active substances in food can effectively regulate the gut microbiota (4)(5)(6), among which insoluble dietary fiber has a good effect on regulating the structure and function of the gut microbiota (7), but there is less research on obesity reduction and its mechanism of action (8,9). At the same time, the structure and function of different sources of dietary fiber vary greatly, and its effect on obesity and its mechanism of action are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The development of obesity is associated with a number of factors, of which the gut microbiota is one of the key factors that has received a lot of attention in recent years and is a potential target for the prevention of obesity and related metabolic diseases. And nutrients and active substances in food can effectively regulate the gut microbiota (4)(5)(6), among which insoluble dietary fiber has a good effect on regulating the structure and function of the gut microbiota (7), but there is less research on obesity reduction and its mechanism of action (8,9). At the same time, the structure and function of different sources of dietary fiber vary greatly, and its effect on obesity and its mechanism of action are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, T2DM is considered to be a chronic inflammatory disease. In many studies related to intestinal inflammation, a significant increase in the abundance of Enterorhabdus has been observed ( Tang et al, 2021 ; Wang et al, 2021 ). It was also found that the abundance of Enterorhabdus was significantly increased in non-alcoholic fatty liver disease (NAFLD) mice ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Firmicutes has been considered as a beneficial bacterium among intestinal microorganisms, the abnormal increase in Firmicutes and the decreased abundance of Bacteroidetes in the diseased group might be caused by obesity, as evidenced by the hepatocyte-filled adipocytes in the pathological sections of the liver diseased group. Increased abundance of Candidatus_Arthromitus is considered as a possible cause of enterocolitis ( Del-Pozo et al., 2010 ; Wang et al., 2021 ). Reduced abundance of colonized probiotic bacteria in the gut weakens the intestinal epithelial barrier and can cause failure of transmission of signals to the host that regulate the immune system ( Bermudez-Brito et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%